Critical Thinking and Mathematical Representation in Dynamics Motion: Instrument Development and Student Profiling in South Sulawesi - Muh Syahrul Padli; Heru Kuswanto; Supardi Supardi (Department of Physics Education, Universitas Mataram, 2026)
The quantitative-descriptive study was conducted to develop instruments for measuring critical thinking and mathematical representation skills, specifically to characterize the student profiles in South Sulawesi based on established indicators in physics learning. The research involved 362 twelfth-grade science students from three randomly selected schools who had completed the Motion Dynamics topic during the first semester of the 2025/2026 academic year. Employing the One-Parameter Logistic (1PL) Item Response Theory, the study confirmed that the developed instruments possess high validity, excellent feasibility, and strong reliability (Person Reliability = 0.75–0.77; Cronbach's Alpha = 0.78) with minimal item bias. Rasch analysis revealed a difficulty range of −0.969 to +1.489 logits, which effectively distinguished between low-, medium-, and high-ability learners. Field test results indicated that students’ skills generally fall within the low-to-moderate range. Specifically, easy items (Items 1, 2, and 7) showed that students have mastered foundational skills, such as gathering information and expressing physics concepts mathematically. Meanwhile, moderate items (Items 3 and 8) demonstrated adequate analytical and problem-formulation abilities. However, items in the difficult and most difficult categories (Items 4–6, 9–10) revealed persistent weaknesses in higher-order thinking, particularly in evaluating conclusions and interpreting mathematical results conceptually.